Some Problems of the Implementation of Administrative Responsibility for Violations of the Legislation on Contract System in the Procurement Sphere - Yuritsin, Andrei E.; Lavrov, Yurii B. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
He article considers the issues of application of Article 6.9 of the Code of Administrative Offences of the Russian Federation and the significance of the practice of implementation of this legal norm to counteraction to illegal drug use. The author estimates the possibility of dealing all cases of illegal use of narcotic drugs and psychotropic substances and their analogues by law enforcement practice as well as the sufficiency of administrative penalties provided for by the Article. Critical evaluation is given to the suitability of criminalization of systematic illegal drug use. The significance of Article 6.9 of the Code of Administrative Offences of RF is connected with the demonstration of the state policy vector regarding illegal drug use, the substantiation of possibility of applying certain measures of state coercion, as well as with the legal statement of the fact of unlawful act and the change of environment in which the offender realizes his/her rights and obligations.